2015
DOI: 10.5539/jas.v7n2p93
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kenaf (Hibiscus cannabinus L.) Leaf, Bark, and Core Extracts on Germination of Five Plant Species

Abstract: The chemical interaction between plants, which is referred to as allelopathy, may result in the inhibition of plant growth and development. The objective of this research was to determine the impact of kenaf (Hibiscus cannabinus L.) plant extracts on the seed germination of five plant species. Four concentrations (0, 16.7, 33.3 and 66.7 g/L) of kenaf leaf, bark, and core extracts were applied to the germination medium of redroot pigweed (Amaranthus retroflexus L.), green bean (Phaseolus vulgaris L.), tomato (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 2 publications
(6 reference statements)
11
7
0
Order By: Relevance
“…Although there is not a clear trend between experiments, all experiments for each of the extract sources produced accelerated hypocotyl growth for green bean plants. These results are consistent with earlier research by Russo et al (1997b) and Webber et al (2015) who observed little or no detrimental impact of kenaf extract concentrations on green bean germination. Also, as reported by Webber et al (2015), there was a slight beneficial impact of the kenaf bark and leaf extracts on seed germination, which is consistent with a potential benefit to post-germination growth of the green bean hypocotyl.…”
Section: Green Bean Hypocotyl Growthsupporting
confidence: 83%
See 4 more Smart Citations
“…Although there is not a clear trend between experiments, all experiments for each of the extract sources produced accelerated hypocotyl growth for green bean plants. These results are consistent with earlier research by Russo et al (1997b) and Webber et al (2015) who observed little or no detrimental impact of kenaf extract concentrations on green bean germination. Also, as reported by Webber et al (2015), there was a slight beneficial impact of the kenaf bark and leaf extracts on seed germination, which is consistent with a potential benefit to post-germination growth of the green bean hypocotyl.…”
Section: Green Bean Hypocotyl Growthsupporting
confidence: 83%
“…These results are consistent with Webber et al (2015), who reported that tomato seed germination decreased as extract concentration increased for different sources of kenaf plant extracts. The core extracts was the least impactful on post-germination growth, while leaf extracts were the most detrimental on hypocotyl and radicle growth, and root numbers (Table 5).…”
Section: Tomato Summarysupporting
confidence: 82%
See 3 more Smart Citations